CHANGES IN GROWTH OF TROPICAL FORESTS: EVALUATING POTENTIAL BIASES - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2002)
Over the past century almost every ecosystem on Earth has come under the influence of changes in atmospheric composition and climate caused by human activity. Tropical forests are among the most productive and extensive ecosystems, and it has been hypothesized that both the dynamics and biomass of apparently undisturbed, old-growth tropical forests have been changing in response to atmospheric changes. Long-term forest sample plots are a critical tool in detecting and monitoring such changes, and our recent analysis of pan-tropical-forest plot data has suggested that the biomass of tropical forests has been increasing, providing a modest negative feedback on the rate of accumulation of atmospheric CO2. However, it has been argued that some of these old forest plot data sets have significant problems in interpretation because of the use of nonstandardized methodologies. In this paper we examine the extent to which potential field methodological errors may bias estimates of total biomass change by detailed examination of tree-by-tree records from up to 120 Neotropical plots to test predictions from theory. Potential positive biases on measurements of biomass change include a bias in site selection, tree deformities introduced by the measurement process, poor methodologies to deal with tree deformities or buttresses, and nonrecording of negative growth increments. We show that, while it is important to improve and standardize methodologies in current and future forest-plot work, any systematic errors introduced by currently identified biases in past studies are small and calculable. We conclude that most tropical-forest plot data are of useful quality, and that the evidence does still weigh conclusively in favor of a recent increase of biomass in old-growth tropical forests.
Keywords: Floresta amazônica; Mudança de clima; Floresta tropical; CNPQ::CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS